Clinical effects and correlates of standard rTMS and theta burst stimulation (TBS) on suicidal ideation in late-life depression - Hyewon H. Lee; Katharina Göke; Rafae A. Wathra; Benoit Mulsant; Alisson P. Trevizol; Jonathan Downar; Shawn M. McClintock; Sean M. Nestor; Yoshihiro Noda; Tarek K. Rajji; Zafiris J. Daskalakis; Daniel M. Blumberger (European Psychiatry)
Abstract Background Previous studies have shown that repetitive transcranial magnetic stimulation (rTMS) can treat suicidal symptoms; however, the effects of rTMS on suicidal ideation (SI) in late-life depression (LLD) have not been well-characterized, particularly with theta burst stimulation (TBS).